The returning tide:: How China, the world's most populous country, is building a competitive research base - Wells, William A. (The Rockefeller University Press, 2007)
When China turned its back on the Cultural Revolution, it aimed to build a thriving capitalist sector. It got one. Now, it wants a world-class research enterprise. How far has it progressed in the biosciences, how did it get there, and how far does it have to go?